Strengthening institutions and governance - International Food Policy Research Institute (International Food Policy Research Institute, 2014)
The centrality of sound institutions and good governance in improving agricultural productivity and reducing rural poverty, hunger, and malnutrition has become widely recognized in recent years. Institutions are the systems of rules that constitute the environment within which policymaking, cooperation, and innovation occur. Governance was defined by the United Nations Development Programme in 1997 as “the exercise of economic, political, and administrative authority to manage a country’s affairs at all levels.” Strong institutions allow for more effective management of commonpool resources and environmental services, while good governance facilitates technical dynamism, gender equity, risk mitigation, and inclusion of the poor in shared growth. Voters queuing inside a polling station in New Delhi, India.